A Sustainability Framework for Social Entrepreneurship through an Indigenous Peoples’ Cooperative: The Case of the Bukidnon-Tagoloanon Tribe - Dinlayan, Loreta Sol; Garcia, Helen; Emata, Annie Leah Roxann L. (Canadian Journal of Nonprofit and Social Economy Research / Revue canadienne de recherche sur les OSBL et l’économie sociale, 2025)
Through this study, the authors developed a framework for Indigenous Peoples’ cooperatives using the experiences of the Bukidnon Tagoloanon Mulahay Ha Kabukalagan Agricultural Cooperative (BUKTAMACO). The Tagoloanon tribe is one of the seven indigenous tribes in Bukidnon, Philippines. The researchers used a case study and ethnographic designs to which the internal and external stakeholders of BUKTAMACO contributed. The results revealed that, to manage its affairs, the tribe followed customary practices like Indigenous leadership, the observance of community values, the concepts of communal property and profit sharing, and concern for the community. Using their experiences, the authors developed a five-pillar sustainability framework that highlighted customary practices as the foundation of this framework. In addition, the role of the Council of Elders was evident in ensuring strength in leadership through consensus building.